Evaluation of native microorganisms degrading non-steroidal anti-inflammatory and psychotropic drugs isolated from wastewater - Palomino Huarcaya , Roger Alberto (2024)
Objective: To select native microorganisms with the ability to degrade non-steroidal anti-inflammatory drugs (Naproxen, Paracetamol, Ibuprofen and Diclofenac) and psychotropic drugs (Carbamazepine, Alprazolam and Clonazepam) from wastewater. Material and Methods: This study examines the degradation of microorganisms in wastewater against anti-inflammatory and psychotropic drugs in Lima. Samples were collected, diluted and plated. After colony verification, degradation capacity was assessed by measuring turbidity and absorbance at 600 nm in a spectrophotometer. Results: Bacterial colonies were analyzed, highlighting characteristics such as white color, circular shape, entire edge, smooth texture, medium size and predominance of gram-positive bacteria. Anti-inflammatory and psychotropic drugs were evaluated, and specific responses of microorganisms were observed. Turbidity in the tubes indicated bacterial growth, with medium turbidity (++) for AINEs and higher turbidity (+++) for psychotropic drugs. Bacterial strains showed variable capacity to degrade drugs, highlighting those with absorbance greater than 1, evidencing growth by drugs as carbon sources. Conclusions: Microorganisms with great potential to degrade drugs found in wastewater.